Structures and processes for adult vaccination services in community pharmacies in Nigeria: Structures et processus des services de vaccination des adultes dans les pharmacies communautaires au Nigéria - Okunlola, Rotkangmwa; Omale, Simeon; Dapar, Maxwell (West African Journal of Pharmacy, 2026)
Background: Community pharmacists are highly accessible health professionals. This accessibility positions pharmacies as logical settings to deliver routine adult vaccinations, accelerate uptake, and decongest other health facilities. To realise this potential, however, pharmacy-based vaccination must be underpinned by clear structures and robust processes.Objectives: This study aimed to identify the structures available for adult vaccination services and the processes followed for community pharmacy services in Nigeria.Methods: This was a descriptive, cross-sectional study. The study population consisted of registered community pharmacies in one state from each of the six geopolitical zones of Nigeria, including Lagos State and the Federal Capital Territory (FCT). Data were collated and entered into Statistical Package for Social Sciences (SPSS) version 25.Results: Most community pharmacies (348,97.2 %) had adequate space for vaccine consultation, facilities for hand washing (311,86.9 %), and sharps disposal (348,97.2 %). Most of the community pharmacists (299,83.5 %) always follow standard operating procedures in administering and handling vaccines.Conclusion: Community pharmacies in Nigeria have relatively adequate structures in place, and mostly follow standardized processes in rendering adult vaccination services. RésuméContexte: Les pharmaciens communautaires sont des professionnels de santé hautement accessibles. Cette accessibilité fait des pharmacies des lieux appropriés pour la prestation des vaccinations de routine chez les adultes, permettant d'en accroître la couverture et de désengorger les autres structures de santé. Toutefois, pour concrétiser ce potentiel, la vaccination en pharmacie doit reposer sur des structures clairement définies et des processus solides.Objectifs: Cette étude visait à identifier les structures disponibles pour les services de vaccination des adultes et les processus suivis par les services de pharmacie communautaire au Nigéria.Méthodes: Il s'agit d'une étude descriptive transversale. La population étudiée était composée de pharmacies communautaires agréées situées dans un État de chacune des six zones géopolitiques du Nigéria, y compris l'État de Lagos et le Territoire de la capitale fédérale (FCT). Les données ont été recueillies et saisies dans le logiciel SPSS (Statistical Package for Social Sciences), version 25.Résultats: La plupart des pharmacies communautaires (348, soit 97.2 %) disposaient d'un espace adéquat pour la consultation vaccinale, d'installations pour le lavage des mains (311, soit 86.9 %) et de dispositifs d'élimination des objets piquants et tranchants (348, soit 97.2 %). La majorité des pharmaciens communautaires (299, soit 83.5 %) respectaient systématiquement les procédures opératoires normalisées pour l'administration et la manipulation des vaccins.Conclusion: Les pharmacies communautaires au Nigéria disposent de structures relativement adéquates et suivent, dans l'ensemble, des processus standardisés pour la prestation de services de vaccination des adultes.